Social-Economic and Social-Demographic Determinants of Alcohol Abuse among Residents of Kajiado County, Kenya - Mukilya, Samuel; Gachohi, John Mwangi; Nyaberi, Jackline Mosinya; Mwiti, Peter Kirimi (Journal of Health, Medicine and Nursing, 2025)
Purpose: The purpose of the study is to determine social-economic and social-demographic factors associated with alcohol abuse among residents of Gataka settlements in Ongata Rongai ward, Kajiado County, Kenya. Methodology: A Cross sectional study design was conducted in Ongata Rongai ward at Kajiado County. Data was collected using a structured interviewer administered questionnaire from the participants. The study population consisted of residents who were above the age of 18 years. The inclusion criteria were residents aged 18 years and above living in Gataka settlements at Kajiado County who gave informed consent to participate in the study. Stratified sampling technique was used to sample the residents based on estates. Both descriptive and inferential statistics were used to analyse data with the aid of SPSS version 22. The results were presented using frequency tables, charts. The study protocol was reviewed and cleared by the University of East Africa Baraton Ethics Review committee with approval no UEAB/08/042019. Findings: The total response rate was 390 (98.9%), majority were males 205(52.6%), married 101(26%), and separated 102(26%). Most of the participants had attained post-secondary education, were not employed (28%), and most 150(38%) earned monthly income of less than USD 50 (Ksh 5,000).The study findings indicated that some socio-demographic and socio-economic factors are predictors of alcohol abuse. Being single or separated was significantly associated with alcohol abuse. Participants with post-secondary education and an income above Kshs.5, 000 were found to be associated with alcohol abuse. Unique Contribution to Theory Practice and Policy: This study has contribute to body of knowledge that individual being single or separated proved to be significantly associated with alcohol abuse. Based on the findings of this study, there is need to assess the root causes of alcohol abuse especially among the young people, address unemployment and put policies in place that enable healthcare systems better detect and address the vulnerabilities of individuals to alcohol abuse.